Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Direktorat Pengembangan Masyarakat Agromaritim IPB University - Dwi Hardana; Muhamad Azis Firdaus; Agung Wibowo (Jurnal Ekonomi dan Bisnis Digital, 2025)
This thesis is the result of research that describes how much influence Leadership Style and Work Motivation have on employee performance at the Directorate of Agromaritime Community Development, IPB University. Leadership is defined as the ability to command, influence and control other people or many people, while work motivation is a stimulus or stimulus for each employee to work in carrying out their duties better. The background behind the author's interest in writing this thesis is based on the results of the author's observations during a 2 month internship, the problem of the directorate of agromaritime community development at IPB University, namely leadership that has not been optimal, lacking direct direction to subordinates, besides that, in the work environment, the facilities provided are still inadequate for employees because work tools and equipment such as hydroponic water pipes are clogged and have not been replaced, damaged doors to the hydroponic area are not immediately repaired and the hydroponic area is always slippery. The results of the author's research used quantitative methods with data collection techniques through distributing questionnaires, with the results that there was a significant influence between the variables of leadership style on employee performance and work motivation. There was no significant influence on employee performance, simultaneously leadership style and work motivation had an influence on employee performance in Directorate of Agromaritim Community Development IPB University.